DESAIN PEMBELAJARAN PENDIDIKAN DASAR BERBASIS PERKEMBANGAN INTELEKTUAL - Irma Fauziah (PREMIERE : Journal of Islamic Elementary Education, 2021)
In the process of implementing elementary school education (SD) or Madrasah Ibtidaiyah (MI), an understanding of the intellectual development of elementary age children is important to become a reference in order to educate and teach. Teaching and learning activities) will be maximized if the teaching material presented can be understood by children. This can happen when the level of material difficulty matches the child's level of thinking ability. So knowledge about the development of thinking skills or intellectual development of elementary age students is something that must be studied. The purpose of this study was to analyze the intellectual development of elementary age students that can be used by teachers and education practitioners as a guide in designing effective learning. This research uses qualitative research methods with the type of literature research. Sources of data used in this research are books, journals, articles and other relevant scientific works. Data were collected and then carried out a descriptive analysis. The result of this research is that intellectual ability is the ability to obtain various information, think abstractly, reason, and act efficiently and effectively. As for intellectual development is influenced by two main factors, namely heredity / heredity and the environment. In the process of providing education, it is important to consider the intellectual development of students at each level as a basis for designing learning. This is because the learning process can take place optimally and the absorption of material by students will be maximized if the materials, media, strategies, models and learning methods used are in accordance with the intellectual abilities of students.